Novel handheld ultrasound technology to enhance non‐expert screening for rheumatic heart disease in the Republic of Palau: A descriptive study. (24th February 2021) - Voleti, Sonia; Adelbai, Myra; Hovis, Ian; Colyer, Jessica; Burns, Kristin M; Lewis, Elway Olkeriil; Arurang, Jason Kalei; Kikuharu, Allyne; Gonzales, Maanne; Pedro, Sheila Judy; Zimmerman, Meghan; Krishnan, Anita; et al.
Abstract : Aim: Non‐expert training in rheumatic heart disease (RHD) detection is a valuable strategy in resource‐limited settings. Here we present an innovative handheld ultrasound application featuring views of correct probe position, imaging protocol and echocardiographic loops of RHD pathology versus normal, accessible during real‐time scanning. Methods: This prospective study was implemented into a pre‐existing school health screening programme at an elementary school in Koror, Palau. Six learners with no prior ultrasound experience were taught a simplified screening protocol in which a mitral regurgitation jet ≥1.5 cm and/or presence of aortic insufficiency were considered a positive screen. All consented children underwent echocardiographic screening by experts with standard portable echocardiography. All positive cases and 25% of negative cases were referred for handheld scans by learners. Results: A total of 26 (4.1%) children were diagnosed with borderline or definite RHD. Mean sensitivity and specificity compared to expert RHD diagnosis over all learners was 71% (standard deviation (SD) 11.3) and 92% (SD 4.9), respectively. For the three highest scanning learners, mean sensitivity was 88% (SD 4.9) and mean specificity was 90% (SD 5.7). For all definite RHD cases, sensitivity was 100% for all but one learner, who achieved sensitivity of 60%. The novel application was used in 229 of 624 (36%) of all handheld scans and 50 of 112 (45%) of expert‐diagnosed positive scans, with protocol and reference features most frequently used. Utilisation of the novel application overall decreased per day of scanning per learner. Conclusion: Adjunctive handheld ultrasound technology may help ease non‐experts into RHD screening.